Identification of Four Secreted Aspartic Protease-Like Proteins Associated With Sophorolipids Synthesis in Starmerella bombicola CGMCC 1576 - Liu, Jun; Zhao, Guoqin; Zhang, Xinyu; Song, Xin (Frontiers in Microbiology, 2021)
The non-pathogenic yeast Starmerella bombicola CGMCC 1576 is an efficient producer of sophorolipids (SLs). The lactonic SLs are mainly produced with yeast extract, and the acidic SLs are mainly produced with ammonium sulfate. Naturally produced SLs are a mixture of various lactonic and acidic SLs. Usually, the SL mixture is not well separated technically, and the separation cost is relatively high. In order to reduce the cost of separation, four secreted aspartic protease-like proteins were identified through proteomic analysis of fermentation broth of S. bombicola under different nitrogen source conditions. The coding genes of the four proteins, namely, sapl1, sapl2, sapl3, and sapl4, are of high sequence similarity (above 55%) and included in a gene cluster. The expression of the four genes was significantly upregulated on (NH4)2SO4 compared with that on yeast extract. The four genes were deleted together to generate a strain Δsapl. The titer of SLs in Δsapl reached 60.71 g/L after 5 days of fermentation using (NH4)2SO4 as the nitrogen source and increased by 90% compared with the wild-type strain. The concentration of acidic SLs was 55.84 g/L, accounting for 92% of the total SLs. The yield of SLs from glucose (g/g) by Δsapl was 0.78, much higher than that by wild-type strain (0.47). However, no increase of SLs production was observed in Δsapl under yeast extract condition. Compared with that of the wild-type strain, the expression levels of the key genes for SLs synthesis were all upregulated to varying degrees in Δsapl under (NH4)2SO4 conditions, and particularly, the expression level of ugta1 encoding UDP glucosyltransferase was upregulated by 14.3-fold. The results suggest that the sapl gene cluster is negatively involved in the production of SLs in the case of (NH4)2SO4 by restraining the expression of the key genes involved in SLs synthesis. The Δsapl strain is an excellent producer of high-titer and high-yield acidic SLs.